Mixed chronic scrotal pain secondary to piriformis scarring treated with PRF: case report - Fangfang Ding; Fengqi Fan; Feng Ji; Hua Xu (Frontiers in Medicine)
In the complex pathological context of mixed pain, where nociceptive, neuropathic, and nociplastic mechanisms coexist and interact, we present an innovative diagnostic and therapeutic model for refractory chronic scrotal pain (CSP) in a 49-year-old man. The pain originated from pudendal nerve entrapment secondary to piriformis scarring. Comprehensive evaluation revealed mixed pain mechanisms: neuropathic (lancinating pain, S2-S4 dermatomal hypoesthesia, and MRI-confirmed nerve compression), nociceptive (MRI-documented proven inflammation and mechanical stress exacerbation), and nociplastic (central sensitization with prolonged pain duration and psychological comorbidities). To address the stratified intervention needs of mixed pain, we implemented a mechanism-targeted strategy that included ultrasound-guided pulsed radiofrequency (PRF, 42 °C/240 s) at the inferior margin of the piriformis muscle to neuromodulate compressed nerves, perineural ozone/steroid injections to modulate the immunoinflammatory microenvironment, and citalopram to manage central sensitization, with complete pain resolution (VAS 8 → 0) sustained at 3-month follow-up. This case uniquely demonstrates how post-surgical piriformis scarring causes tripartite pain pathogenesis through neuro-immune-myofascial interactions, such as mechanical nerve compression, local inflammation, and subsequent central sensitization. The therapeutic strategy synergistically addressed all three cascades of mechanisms via C-fiber modulation, reduction of pro-inflammatory cytokines, and reversal of neuroplasticity. This study advances the understanding of CSP etiology beyond idiopathic causes by providing a reproducible mechanism-based precision model for mixed pain syndromes and advocating for multidisciplinary management that integrates interventional techniques, pharmacotherapy, and psychorehabilitation.